The Relationship between Purchase Experience and Online Purchase Behaviour - Siti Aisyah Salim; Tan Yun Qi (Research in Management of Technology and Business, 2024)
With the rapid development of the Internet and social media, it is now much easier than before to purchase anything on the Internet. Online shopping, often referred to as buying and selling items through the Internet, is a process of purchasing goods directly from a seller without the use of an intermediary. Therefore, the study aims to explore the relationship between purchase experience and online purchase behaviour among the Generation Y in Kuala Lumpur. The four types of online purchase experience are delivery, packaging, customer support, return and exchange, the target respondents of this study are Generation Y which was born between 1982 and 1994. This research provided one dependent variable which is online purchase behaviour and independent variable which are delivery, packaging, and customer support. This study used randomly selecting respondents from the population Generation Y without any specific criteria or stratification. Thus, a total of 384 respondents of Generation Y in Kuala Lumpur must answer the questionnaire which will be distributed via Google form. This study encompassed a sample of 351 respondents from Generation Y in Kuala Lumpur, employing a quantitative research method. The data collection involved the utilization of a self-administered questionnaire and an online survey. The collected data underwent analysis using the Statistical Package for Social Science (SPSS), enabling the generation of quantitative reports represented through frequency, percentage, mean, and standard deviation. This study helps marketers to understand the best marketing strategy to adopt, especially Generation Y. As a result, all variables have a significant relationship with online purchase behaviour and delivery refers to the purchase experience that can give a great experience to consumers has the highest correlation coefficient of 0.256.